PERANCANGAN MOCK UP SISTEM INFORMASI MANAJEMEN DESA BERBASIS WEBSITE (STUDI DI DESA MEKARMUKTI KECAMATAN CISAGA KABUPATEN CIAMIS JAWA BARAT) - Nanang Pradita; Miftahul Huda; Rahmat Hidayat (LPPM Unbaja, 2024)
Mekarmukti Village is located in Cisaga District, Ciamis Regency, West Java, Indonesia. The village is famous for its natural beauty and cultural heritage, as well as its agricultural practices. The village is surrounded by lush green forests and hills, making it a popular destination for tourists looking to explore the natural beauty of West Java. One issue that often arises in the Mekarmukti Village community that is the focus of attention is the lack of clarity of information conveyed to residents, causing them to repeatedly seek information. The village government has difficulty collecting family data due to various reasons and the busyness faced by residents, hampering the performance of the village government. From the above problems, the purpose of study is designing a Website-based Information System that is used to facilitate the Mekarmukti Village community in getting or obtaining the latest information from the Village Government. In addition to making it easier to get information, this information system also provides information related to tourist info and tourist maps, as well as financial transparency of Mekarmukti Village.